FAKTOR YANG MEMPENGARUHI KECEMASAN PERAWAT TERHADAP COVID-19 DI RUANG RAWAT INAP RSKD DADI PROV. SUL-SEL - Zulkifli; Resky Fajriah (Institut Kesehatan Pelamonia, 2022)
Anxiety is a form of feeling worried, anxious and other unpleasant feelings, anxiety often arises in individuals when faced with unpleasant situations. This research aims to to find out whether there is a significant influence on the Factors Affecting Nurse Anxiety in Efforts to prevent Covid-19 in the Dadi Hospital Inpatient Room, South Sulawesi Province. The type of research used is quantitative research with a cross sectional research design, with the number of respondents as many as 138 hospital nurses. The data was collected through the distribution of questionnaires directly to the respondents. Data analysis is done by using the chis square test. The results showed that there was a significant relationship with prevention of spread, including the threat of physical integrity p= 0.033, self-system threat p=0.035, stress p=0.023, environment p=0.001 with preventing the spread of the covid-19 virus. It is recommended to hospitals to pay more attention to the protocol of Covid-19 for nurses to provide good comfort.